2018
DOI: 10.1186/s12911-018-0602-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinical decision rules, patient cost and malpractice information on clinician brain CT image ordering: a randomized controlled trial

Abstract: BackgroundThe frequency of head computed tomography (CT) imaging for mild head trauma patients has raised safety and cost concerns. Validated clinical decision rules exist in the published literature and on-line sources to guide medical image ordering but are often not used by emergency department (ED) clinicians. Using simulation, we explored whether the presentation of a clinical decision rule (i.e. Canadian CT Head Rule - CCHR), findings from malpractice cases related to clinicians not ordering CT imaging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…The 12 selected articles reported on 10 distinct studies. Among these studies, three addressed monitoring and individual feedback [32][33][34], two compared framed presentations [35,36], two addressed heuristics [37,38] and [39], one was about social norms [40], one addressed the ordering effect [41], and one used a combination of overconfidence, risk aversion, and herding [42,43]. Figure 1 presents the flowchart of this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12 selected articles reported on 10 distinct studies. Among these studies, three addressed monitoring and individual feedback [32][33][34], two compared framed presentations [35,36], two addressed heuristics [37,38] and [39], one was about social norms [40], one addressed the ordering effect [41], and one used a combination of overconfidence, risk aversion, and herding [42,43]. Figure 1 presents the flowchart of this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…While no differences were found in terms of changes in intentions and other outcomes, the authors found that the format of numbers plus a framed presentation was effective for numerate patients. A very recent study [36] found that the ordering of advanced medical imaging procedures was affected by framed information designed to show physicians guideline rules, malpractice cases, and costs.…”
Section: Decisions Influenced By Other Colleaguesmentioning
confidence: 99%
“…A multidisciplinary team approach and a reduction in head CT scans with use of the CCHR are consistent with data from previously published studies. [14][15][16] The clinical decision pathway created for this project is in alignment with the American College of Emergency Physicians' current recommendations on the management of patients who present with minor head injury. 3,6 Using the CCHR within the pathway, all patients with brain injuries were properly risk stratified.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a decrease of head CT imaging use by 7.8%. 15 Gimbel et al 16 used vignette case study stimulations in which clinicians made an initial imaging decision followed by education on CCHR application and an opportunity to modify the initial order. This approach led to a 21.1% reduction in head CT use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation